I'm having trouble with whether Rudin actually proves what he's tried to prove.

Proposition 1.14; (page 6) The axioms of addition imply the following statements:

a) if $x + y = x + z$ then $y = z$

The author's proof is as follows: $ y = (0 + y) = (x + -x) + y = -x + (x + \textbf{y})$ $$ = -x + (x + \textbf{z}) = (-x + x) + z = (0 + z) = z $$

I emphased the section which troubles me. How does Rudin prove that $ y = z $ if he substituted $y = z$?

  • 7
    $\begingroup$ He just used the assumption that $x +y = x + z$. That's why he used associativity (shifted the brackets) in the first place. $\endgroup$
    – Student
    Feb 6 '17 at 11:05
  • 2
    $\begingroup$ Note that in any proof, you should expect the original assumption to show up somewhere in the proof; otherwise, it would seem that the proof holds without the original assumption, in which case you've proved a tautology. (I.e. when proving $P \implies Q$, if $P$ is not used in your proof, then you've proved that $Q$ is always true.) $\endgroup$ Feb 6 '17 at 19:07

He didn't substitute $z$ for $y$; rather, he substituted $x+z$ for $x+y$. This is legitimate based on the assumption that $x+y = x+z$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.